Single-nucleus RNA sequencing reveals dynamic changes in the microenvironment of visceral adipose tissue and metabolic characteristics after cold exposure - Yi, Ting; Wu, Shuai; Yang, Yusha; Li, Xi; Yang, Shuran; Zhang, Yongqiang; Zhang, Li; Hu, Yuyu; Zhang, Guanyu; Li, Jun; Yang, Danfeng (Frontiers in Endocrinology, 2025)
IntroductionVisceral adipose tissue (VAT) plays a crucial role in regulating systemic metabolic balance. Excess accumulation of VAT is closely associated with various metabolic disorders, a process that involves the coordinated actions of multiple cell types within the tissue. Cold exposure, as a potential intervention, has been proposed to improve metabolic dysfunction. However, the heterogeneity of VAT and its comprehensive metabolic characteristics under cold exposure remain unclear.MethodsWe collected epididymal white adipose tissue (eWAT) of C57BL/6J mice after cold exposure at three different time points for single-nucleus RNA sequencing (snRNA-seq) analysis.ResultsWe successfully identified ten major cell types in eWAT, enabling understanding of the dynamic changes in the eWAT microenvironment and its metabolic features during cold exposure. This study revealed that cold exposure for 1 day reduced cellular metabolic activity and intercellular communication in eWAT including receptor-ligand-based cell communication and metabolite-mediated interactions. However, after 14 days of cold acclimation, the metabolic activity of adipocytes was significantly enhanced, and intercellular metabolic communication was restored. Additionally, prolonged cold exposure promoted the formation of a distinct adipocyte subpopulation that may be associated with UCP1-independent thermogenesis. These changes may be a new homeostatic state established by VAT to adapt to the cold environment. The study also identified the importance of adipocytes, adipose stem and progenitor cells, myeloid cells, and endothelial cells in the process of cold adaptation.DiscussionThis research provides valuable insights into the cellular heterogeneity, adipocyte remodeling, and metabolic reprogramming in eWAT after cold exposure. It highlights the critical role of transcriptional dynamics in eWAT during cold exposure and provides new perspectives on the prevention and treatment of metabolic diseases.